Kinetic characterization of a novel cysteine peptidase from the protozoan Babesia bovis, a potential target for drug design - Lu, Stephen; Ascencio, Mariano; Torquato, Ricardo J.S.; Florin-Christensen, Mónica; Tanaka, Aparecida S. (Elsevier, 2022)
C1A cysteine peptidases have been shown to play an important role during apicomplexan invasion and egress of host red blood cells (RBCs) and therefore have been exploited as targets for drug development, in which peptidase specificity is deterministic. Babesia bovis genome is currently available and from the 17 putative cysteine peptidases annotated four belong to the C1A subfamily. In this study, we describe the biochemical characterization of a C1A cysteine peptidase, named here BbCp (B. bovis cysteine peptidase) and evaluate its possible participation in the parasite asexual cycle in host RBCs. The recombinant protein was obtained in bacterial inclusion bodies and after a refolding process, presented typical kinetic features of the cysteine peptidase family, enhanced activity in the presence of a reducing agent, optimum pH between 6.5 and 7.0 and was inhibited by cystatins from R. microplus. Moreover, rBbCp substrate specificity evaluation using a peptide phage display library showed a preference for Val > Leu > Phe. Finally, antibodies anti-rBbCp were able to interfere with B. bovis growth in vitro, which highlights the BbCp as a potential target for drug design.